Isoproterenol Increases Left Atrial Fibrosis and Susceptibility to Atrial Fibrillation by Inducing Atrial Ischemic Infarction in Rats - Ma, Shiyu; Ma, Jin; Tu, Qingqiang; Zheng, Chaoyang; Chen, Qiuxiong; Lv, Weihui (Frontiers in Pharmacology, 2020)
Left atrial (LA) fibrosis is a major arrhythmogenic substrate for atrial fibrillation (AF). The purpose of this study was to assess whether isoproterenol (ISO) induces LA fibrosis and increases susceptibility to AF, exploring the underlying mechanisms. Male Sprague-Dawley rats were subcutaneously injected ISO once per day for two days. Five weeks after injection, the ISO group had higher susceptibility AF and prolonged AF duration compared with the control group. ISO decreased LA conduction velocity and increased LA conduction heterogeneity. ISO increased fibrosise areas and the protein levels of collagen types I and III in the left atrium. Anti-fibrosis drug pirfenidone decreased AF occurrence and reduced LA fibrosis in ISO treated rats. ISO injection induced atrial ischemia infarction by increasing heart rate and decreasing diastolic and systolic blood pressures. These findings demonstrated that ISO increases susceptibility to AF by increasing LA fibrosis and LA conduction abnormalities five weeks after injection. ISO injection induces atrial ischemic injury is the main cause of fibrosis. Rats with ISO-induced LA fibrosis may be used in further AF research.